2014
DOI: 10.1097/jsm.0000000000000095
|View full text |Cite
|
Sign up to set email alerts
|

A New Technique Using Fibrin Glue in the Management of Auricular Hematoma

Abstract: : This study aims to describe a new technique for the management of auricular hematoma using fibrin glue. Five difficult cases of auricular hematoma were managed using this technique, including 2 recurrent and 3 delayed presentations. After skin preparation and local anesthetic, an incision was made, the hematoma was evacuated, and the cavity was washed out with saline. Fibrin glue was applied liberally; a dental roll pressure dressing was applied and secured with a prolene bead suture. The patients were given… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 8 publications
0
4
0
1
Order By: Relevance
“…New techniques using fibrin glue and an 18-gauge catheter with a compression dressing are recently proposed. Cost-effectiveness and efficacy of these management options remain to be confirmed by further studies ( 20 , 21 ).Use of local flaps in soft tissue defects, initial realigning of the helical rim and anatomical repair of ear lacerations should be considered in management of acute ear trauma. In cases of ear amputation, staged reconstruction or replantation techniques should be used ( 22 ).…”
Section: Resultsmentioning
confidence: 99%
“…New techniques using fibrin glue and an 18-gauge catheter with a compression dressing are recently proposed. Cost-effectiveness and efficacy of these management options remain to be confirmed by further studies ( 20 , 21 ).Use of local flaps in soft tissue defects, initial realigning of the helical rim and anatomical repair of ear lacerations should be considered in management of acute ear trauma. In cases of ear amputation, staged reconstruction or replantation techniques should be used ( 22 ).…”
Section: Resultsmentioning
confidence: 99%
“…ello se realizará una incisión que se asentará en alguno de los surcos del pabellón en relación íntima con el acúmulo, para evitar al máximo las cicatrices no estéticas 12 .…”
Section: Discussionunclassified
“…The study of Kram et al demonstrated that gentamicin and neomycin extend clotting time. In conclusion, the properties of the clot as well as time of clot formation should always be checked in laboratory setting before using fibrin glue as a drug delivery system [7,14,[23][24][25].…”
Section: Fibrin Glue As Carrier Of Active Substancesmentioning
confidence: 99%
“…Endoscopic injections of fibrin glue were used by physicians from several Iranian centers for pharyngocutaneous fistula (PCF) removal after complete laryngectomy. Fistula closure was reported after a month which suggests that fibrin glue can be effectively used for fistula repair in otolaryngology [9,25,[39][40][41][42].…”
Section: Other Applications Of Fibrin Gluementioning
confidence: 99%